Implementation of the Design Thinking Method in Designing a Laboratory Room Scheduling System - Nindy Raisa Hanum; Hasanatul Iftitah; Yogi Perdana (Journal of Informatics and Communication Technology (JICT), 2025)
Laboratories are essential facilities in higher education institutions, particularly in supporting practical learning and research activities. However, manual management often leads to scheduling conflicts, inefficient room utilization, and limited access to real-time information. This study aims to develop a web-based, integrated laboratory room scheduling system for the Faculty of Science and Technology at the University of Jambi. The research adopts the Design Thinking methodology, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Stakeholder needs were identified through interviews with lecturers, students, lab staff, and laboratory heads. The primary issue identified was the lack of a centralized scheduling system. A prototype was designed using Figma, incorporating features such as real-time schedule viewing, room booking management, and usage reporting. Usability testing with five respondents revealed high satisfaction in terms of learnability (84%), memorability (85%), and efficiency (87%). The results confirm that the system meets user needs and improves laboratory management. This study contributes to the digital transformation of academic services by offering a user-centered, context-aware solution tailored to the needs of the Faculty of Science and Technology.